Improvement of oxygen permeation through microchanneled ceramic membranes - Shao, Xin; Dong, Dehua; Parkinson, Alan; Li, Chun-Zhu (Elsevier BV, 2014)
Microchanneled membranes have demonstrated high oxygen permeation fluxes owing to the shortened oxygen permeation distance and the enlarged membrane surface area. In this study, further improvement of the oxygen permeation flux has been attempted through using dual-phase membranes and applying catalysts on the membrane surfaces. Compared with pure La0.6Sr0.4Co0.2Fe0.8O3-δ (LSCF) membranes, LSCF–Ce0.8Gd0.2O2-δ (GDC) dual-phase membranes increased oxygen flux by 57% due to the balanced oxygen ionic and electronic conductivities. The open microchannel structure facilitated the coating of catalysts on both sides of the membranes because catalyst can readily be delivered to the membrane surface on the microchannel side through the numerous microchannels. The catalyst increased the oxygen fluxes of both pure LSCF membranes and dual-phase membranes, while it had a larger effect on the dual-phase membranes because its surface reactions play a more significant role in controlling the overall oxygen permeation. Finally, the improvements increased oxygen flux through the microchanneled membranes from 1.4 to 3.8 ml cm-2 min-1 at 950°C, i.e. by a factor of 2.7.